Child ‘streetism’ through Kinaesthetics (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The term child ‘streetism’ refer to a group of children that has emerged as a result of rapid technological development that led to the migration of people from rural areas to cities. However, due to various other factors that thwart efforts to improve their lives, a class of street children is emerging. This paper examines the children living on the streets in Malaysia. They are subjected to multiple forms of abuse, neglect and often engage in informal economic activities to survive. Children basic needs can be effectively met through empowerment and holistic approaches that utilize art and creativity. Such approaches recognize that children’s well-being is linked to various aspects of their lives, such as physical, emotional and social. Arts and creativity provide street children with a safe space for self-expression, increase self confidence and self-esteem, develop life skills, and create alternative income opportunities. In addition, arts and creativity-based interventions have been shown to promote positive mental health outcomes, improve social inclusion and reduce stigma among street children. This study draws on several perspectives on the issue of child ‘streetism’ in Malaysia. However, the mandatory focus is about analysing the empowerment and holistic approach to children’s ‘streetism’ via art and creativity in education to help children realize their full potential and overcome their obstacles. Interviews, and thematic analysis will be conducted to obtain a collective opinion and gather more information on the research topic. Arts and creativity via education can play an important role in addressing the challenges faced by children living in the streets, by providing opportunities for self-expression, skill development, social inclusion, trauma recovery, advocacy and especially education. Ultimately, by incorporating Kinaesthetic Learning methods via arts and creativity can empower them, promote their well-being and contribute to their holistic development which can be effective strategies to foster the resilience of the street children and help them to build a better future.
Keywords: Art; Children; Creativity; Kineasthetics; Streetism